Genomic characterisation of generic Escherichia coli from food-producing animals and products of animal origin in South Africa - Malesa, Refiloe; Pierneef, Rian; Magwedere, Kudakwashe; Mafuna, Thendo; Matle, Itumeleng (Frontiers in Bacteriology, 2024)
Escherichia coli is found in diverse environmental niches, including meat and meat products, and is known for its significance in both food safety and public health. In South Africa, whole genomic sequencing (WGS) efforts for E. coli are overwhelmingly skewed toward human isolates with limited studies conducted on non-human isolates. Therefore, the aim of this study was to use WGS to characterize generic strains of E. coli isolated from animal specimens, meat, and meat-based products in South Africa. Based on WGS analysis, a total of 35 E. coli strains were grouped into five phylogroups (A, B1, B2, C, and E), with A (46 %) being the most predominant. Virulence-associated genes identified the isolates as either extra-intestinal pathogenic E. coli (69 %) or intestinal pathogenic E. coli (31 %) pathotypes. Twenty-three different serotypes were identified, with O101:H37 (17 %), O2:H4 (17 %), O6:H5 (13 %), and O64:H19 (9 %) being the predominant ones. Among the 19 different sequence types (STs), ST1858, ST975, and ST10 were the most prevalent (11% each). Various virulence genes, antimicrobial resistance genes, and genetic mobile elements carrying Tn2, IS26, and Tn6196 elements were detected, with the disinfectant resistance sitABCD being the most predominant.The type 1 CRISPR system which functions by storing records of previous invasions to provide immunological memory for a rapid and robust response upon subsequent viral infections was detected in all isolates, consisting of subtypes I-E (86%), I-A (57%), and I-F (11%). The findings of this study provide an insight into the genetic diversity of generic E. coli isolates from animal species, meat, and meat-based products in South Africa.